1995
DOI: 10.1016/0895-7061(95)00364-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific cardiovascular adaptation due to circadian blood pressure variations in essential hypertension

Abstract: To determine the effects of circadian variation in arterial pressure on early hypertensive target organ disease, we examined systemic hemodynamics (cardiac output by indocyanine green dye dilution), renal hemodynamics (renal plasma flow by iodine-131 para-aminohippuric acid clearance), left ventricular structure and function (2D-guided M-mode echocardiogram), and 24-h ambulatory blood pressure in 20 women and 46 men with untreated essential hypertension. Both gender groups were subdivided into "dippers" and "n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 32 publications
3
37
0
1
Order By: Relevance
“…We also combined data for men and women regardless of the fact that the associations between left ventricular mass and the day-night blood pressure difference may differ between men and women. 33 Furthermore, in this study, the antihypertensive treatment was not interrupted several weeks prior to the study measurements, contrary to what is done in most studies. 4 These differences in study design could explain the low correlation coefficients.…”
Section: Discussionmentioning
confidence: 90%
“…We also combined data for men and women regardless of the fact that the associations between left ventricular mass and the day-night blood pressure difference may differ between men and women. 33 Furthermore, in this study, the antihypertensive treatment was not interrupted several weeks prior to the study measurements, contrary to what is done in most studies. 4 These differences in study design could explain the low correlation coefficients.…”
Section: Discussionmentioning
confidence: 90%
“…In studies examining dipping status and hypertensive target organ damage, researchers found that LVM increased with ambulatory BP in women and men. However, this increase in LVM and LVMI was linked to the absence of a normal nocturnal BP fall in women only (24,(29)(30)(31). The findings remained statistically significant after adjustment for average 24 h BP values, thereby suggesting that cardiac abnormalities may be more closely related to an altered diurnal BP rhythm rather than a higher average BP over 24 h. These data may be particularly significant, given that a nondipping BP profile has been found to be more common in hypertensive women with future cardiovascular complications (41).…”
Section: Mass and The LV Mass Indexmentioning
confidence: 99%
“…Schmieder et al (24) found that female hypertensive nondippers had significantly greater relative wall thickness, posterior wall thickness and concentric LVH than female hypertensive dippers and male hypertensive dippers and nondippers. Even after controlling for age, body weight and 24 h BP, the differences were maintained (24).…”
Section: Cardiac Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…18 In addition, in women, an association between BP variation and cardiac abnormalities has been reported in hypertensive dippers and nondippers. 47 These findings suggest that the effects of age and sex on surge should be considered further in hypertensive patients.…”
Section: Discussionmentioning
confidence: 95%